The Influence of Job Insecurity and Burnout on Turnover Intentions of Hotel Employees in Palopo - Rahmat Rahmat; Ahmad Syarief Iskandar (International Journal of Artificial Intelligence Research, 2022)
The purpose of this study was to analyze the relationship between job insecurity variables and turnover intentions, the relationship between burnout variables and the turnover intentions of hotel employees in Palopo. sampling. Data was obtained by distributing online questionnaires with a Likert scale of 1 to 7 through social media. The analysis technique used Structural Equation Modeling (SEM) with data processing tools SmartPLS 3.0 software. The independent variable in this study is job insecurity and burnout, while the independent variable is turnover intentions. The increase in the Job Insecurity variable has an insignificant effect on the turnover intentions variable. There is a significant influence between burnout on the turnover intentions of hotel employees in Palopo.